(untitled) (SCIENCE TIME JOURNAL, 2026)
This article investigates the artistic and psychological portrayal of female consciousness in the novels of Virginia Woolf, focusing on the inner life, emotional complexity, and identity formation of her female characters. Woolf’s modernist techniques, including stream-of-consciousness, interior monologue, and narrative fragmentation, allow a profound exploration of the inner psyche and social pressures influencing women’s experiences. The study examines key works such as Mrs. Dalloway, To the Lighthouse, and Orlando, highlighting the interplay between personal identity, societal expectations, and historical context. Through comparative analysis, the article situates Woolf’s contribution within modernist literature while exploring feminist perspectives and psychological realism. Findings indicate that Woolf’s innovative narrative strategies illuminate female consciousness in ways that challenge traditional gender norms, offering enduring insights into the complexity of women’s inner lives.